2003
DOI: 10.1016/s0891-5245(02)88328-6
|View full text |Cite
|
Sign up to set email alerts
|

Computer game for inner-city children does not improve asthma outcomes

Abstract: Findings indicate that this CAI game was not effective in improving asthma symptoms in this group of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the study characteristics in terms of adherence and self-management (including self-management efficacy, beliefs and behaviours) outcomes. Five studies (31%) did not report on behavioural outcomes [50,53,55,57,63].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the studies focused on children, most address interventions for school-aged children [13][14][15][16][17][18][19][20][21][22]. The literature is lacking in studies addressing the creation of education material for children, especially those that include information about self-regulating behaviors.…”
Section: Audience: Childrenmentioning
confidence: 99%
“…A landmark study by Rubin et al evaluated children who used a program entitled Asthma Command and reported asthma knowledge and medical selfmanagement behaviors increased in children enrolled in the program [82]. Following the success of Asthma Command, several other programs-including Watch, Discover, Think, Act; Wee Willie Wheezie; Bronkie the Bronchiasauras; The Asthma Files; Okay With Asthma; and Okay With Asthma 2.0-were developed and tested [14,15,17,19,20,22]. Children age seven to 18 years were tested on their asthma knowledge, symptom management, behavioral responses, and overall feelings towards their chronic disease and they improved in all of these areas after using electronic education games [14,19,20,82].…”
Section: Electronic Educational Gamesmentioning
confidence: 99%
See 1 more Smart Citation